Mo-doped La0·6Sr0·4FeO3-δ as an efficient fuel electrode for direct electrolysis of CO2 in solid oxide electrolysis cells. (20th March 2020) - Wang, Shun; Jiang, Huaguo; Gu, Yiheng; Yin, Bo; Chen, Sainan; Shen, Muyi; Zheng, Yifeng; Ge, Lin; Chen, Han; Guo, Lucun
Abstract: Conversion of CO2 into CO in solid oxide electrolysis cells (SOECs) at high temperatures is an attractive route for CO2 utilization and intermittent renewable resource storage. In this study, La0·6 Sr0·4 Fe1-x Mox O3-δ -Gd0.1 Ce0·9 O2-δ (LSFMx -GDC; x = 0, 0.05, 0.10, 0.15) composites are evaluated as fuel electrodes of SOECs for the direct electrolysis of CO2 . XRD results show that the lattice parameters slightly increase with increasing Mo doping content, x, and that the solid-solution concentration of Mo in LSFMx is limited to x ≤ 0.1. LSFMx shows good chemical compatibility with GDC and excellent stability without decomposition under a CO2 or reducing atmosphere. The optimal electrode composition with x = 0.05 exhibits minimal polarization resistance at 600–800 °C. A current density of 1.06 A cm −2 at 1.5 V and 800 °C is achieved by the LSFM0.05 -GDC fuel electrode in an electrolyte-supported single cell; this current density represents an increase of approximately 50% compared with that obtained using a non-Mo-doped electrode. The mechanism of the effect of Mo doping is also investigated, and the results of X-ray photoelectron spectroscopy, temperature-programmed desorption of CO2, and analysis of the distribution of relaxation time reveal that introduction of Mo promotes the formation of oxygen vacancies, which enhance CO2 adsorption and improve the diffusion and exchange of oxygen species. Such improvement ultimately accelerates surface reaction kinetics.